2020
DOI: 10.1007/s10658-020-02043-4
|View full text |Cite
|
Sign up to set email alerts
|

Neofabraea kienholzii, a novel causal agent of grapevine trunk diseases in Hungary

Abstract: Recently, more and more new fungal pathogens have been described as causal agents of grapevine trunk diseases (GTDs), which lead to increasingly significant economic losses in viticulture worldwide. The genus Neofabraea consists of species mainly known as important plant pathogens causing perennial canker and bull's eye rot, a common postharvest disease of apple (Malus domestica) and pear (Pyrus communis) fruits. Neofabraea kienholzii also causes lesions on pome fruits and canker on woody tissues, but its path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
(45 reference statements)
0
3
0
Order By: Relevance
“…were recently shown to be associated with decline ( K. variispora ) and vascular necrosis ( K. longispora ) of V. vinifera [ 30 , 102 ]. Further taxa that were identified at genus level only in our study are Seimatosporium , Neofabrea , and Truncatella ; related species known as pathogens on grapevine are S. vitis , N. kienholzii , T. angustata [ 29 , 103 , 104 , 105 , 106 , 107 , 108 ]. Apart from the above pathogens, a fungal genus with strong potential for biological control against GTD fungi, i.e., Clonostachys , was found [ 109 , 110 ].…”
Section: Discussionmentioning
confidence: 82%
“…were recently shown to be associated with decline ( K. variispora ) and vascular necrosis ( K. longispora ) of V. vinifera [ 30 , 102 ]. Further taxa that were identified at genus level only in our study are Seimatosporium , Neofabrea , and Truncatella ; related species known as pathogens on grapevine are S. vitis , N. kienholzii , T. angustata [ 29 , 103 , 104 , 105 , 106 , 107 , 108 ]. Apart from the above pathogens, a fungal genus with strong potential for biological control against GTD fungi, i.e., Clonostachys , was found [ 109 , 110 ].…”
Section: Discussionmentioning
confidence: 82%
“…However, most of these interactions between fungi and grapevine are not welldocumented, as in the case of Sporocadus, Pestalotiopsis, Dendrothyrium, and Truncatella, among other genera, whose role in the GTD process and/or infection is still not clarified (Arzanlou et al, 2013b;Abed-Ashtiani et al, 2019;Mundy et al, 2020). Additionally, studies performed in Hungary showed that fungi genera are emerging continuously, affecting canonically other woody hosts, such as apple and pear, that may cause symptoms similar to those observed in GTDs, namely, Pseudofabraea, Phlyctema, Parafabraea, and Neofabraea, thus increasing the intricacy of this disease complex (Lengyel et al, 2020). Furthermore, fungal identification from wounded tissues may show activity from saprobic or endophytic fungi upon tissues with less integrity that might have no role in the infectious and colonization processes (e.g., Trametes versicolor in necrotic tissue of GTD-affected vines) (Mundy et al, 2020).…”
Section: Fungal Interactions With Grapevine Trunk Disease (Gtd) Patho...mentioning
confidence: 99%
“…Current knowledge of fungal species related to GTDs (Phillips, 1998;Fischer and Kassemeyer, 2003;van Niekerk et al, 2004;Halleen et al, 2007;Alaniz et al, 2009;Tomoiaga et al, 2009;Úrbez-Torres and Gubler, 2009;Trouillas and Gubler, 2010b;Luque et al, 2012;Arzanlou et al, 2013a,b;Úrbez-Torres et al, 2013;Linaldeddu et al, 2014;Rolshausen et al, 2014;Arzanlou and Narmani, 2015;Cloete et al, 2015;Travadon et al, 2015;Maharachchikumbura et al, 2016;Carlucci et al, 2017;da Silva et al, 2017;Lawrence et al, 2017, Halleen et al, 2007Pouzoulet et al, 2017;Váczy et al, 2017;Guarnaccia et al, 2018;Moyo et al, 2018Moyo et al, , 2019Pintos et al, 2018;Rezgui et al, 2018;Abed-Ashtiani et al, 2019;Akgül et al, 2019;Lesuthu et al, 2019;Manawasinghe et al, 2019;Raimondo et al, 2019;Amarloo et al, 2020;Berlanas et al, 2020;Brown et al, 2020;Lengyel et al, 2020;Mundy et al, 2020). Taxonomic synonyms of interest were obtained from Mycobank (2021) database (www.mycobank.org).…”
Section: Author Contributionsmentioning
confidence: 99%